Emisión de compuestos orgánicos volátiles (voc) durante el compostaje de biosólidos provenientes de plantas de tratamiento de aguas residuales domésticas - Ramos, Claudia Ximena; Estévez, Sandra; Giraldo, Eugenio (Revista de Ingeniería, 2001)
This work presents the results of VOC’s emitted during the wastewater biosolids composting in two static piles. VOC’s were isolated by Solid Phase Microextraction (SPME) and analysed by Gas Chromatography/Mass Spectrometry (GC/MS). More than 150 organic compounds were identified including aliphatic and aromatic hydrocarbons, chlorinated compounds, ketones, mercaptans, sulfides, alcohols and amines, a must of them in concentration above the USEPA inhalation standards.